OPTIMUM LOCATION ANALYSIS OF STORY ISOLATION SYSTEM ON HIGH RISE BUILDING - Muhammad Reza, Alif
Various studies have been carried out to understand the feasibility and mechanisms of the story isolation system. The results obtained are also quite interesting, the use of the story isolation system results in better story drift reduction than the base isolation system. However, these studies only focused on low-rise buildings, even though the story isolation system will be more attractive if it can also be used in high-rise buildings. In this study, numerical analysis was carried out on 30-, 40-, 50-, and 60-story buildings to find the location of the story isolator which resulted in the highest reduction of story drift and story shear. Then a general solution is sought so that it can become a reference for buildings with different plans and height.